Biodegradable resin composition and biodegradable resin molded article
Patent Information
- Application Number
- JP2021088575
- Authority / Receiving Office
- JP · JP
- Patent Type
- Patents
- Current Assignee / Owner
- Priority Date
- 2020-06-02
- Filing Date
- 2021-05-26
- Publication Date
- 2025-01-15
- Estimated Expiration
- 2041-05-26
AI Technical Summary
【0020】 本発明の生分解性樹脂組成物によれば、ホームコンポストの条件においても生分解性が良好であることから、従来の生分解性樹脂に比べてホームコンポスト材として適用しやすい。また、生分解性樹脂(X)とセルロース誘導体(Y)との相溶性もよいことから、成形体とした際の外観や手触りに優れる。
Smart Images

Figure 0007613268000001 
Figure 0007613268000002
Abstract
Description
[Technical field]
[0001] The present invention relates to a biodegradable resin composition which uses raw materials derived from plants and has excellent compatibility and biodegradability, and to a biodegradable resin molded article obtained by extrusion molding or injection molding of this biodegradable resin composition. [Background technology]
[0002] In recent years, concerns about ecosystem and environmental pollution due to the disposal of plastic products in the ocean, etc., have become apparent. Various regulations are being enacted in countries around the world from the perspective of preventing environmental pollution. For example, in Europe, regulations and laws are being enacted that prohibit the use of disposable plastic shopping bags and disposable plastic containers such as cups and plates in retail businesses. In order to be exempt from the use ban measures under this law, it is necessary for the product to be made from biomass with a minimum biomass content or more set here as a raw material and to be compostable in ordinary households (home compostable products). Recently, there has also been a demand for marine biodegradable plastic products, which decompose even in the sea if plastic products are discharged into the ocean.
[0003] Conventionally, known examples of biodegradable plastics (resins) include aliphatic-aromatic polyesters such as polybutylene terephthalate / adipate (hereinafter abbreviated as PBAT) and polybutylene succinate / terephthalate (hereinafter abbreviated as PBST), aliphatic polyesters such as polylactic acid (hereinafter abbreviated as PLA), polybutylene succinate (hereinafter abbreviated as PBS) and polybutylene succinate / adipate (hereinafter abbreviated as PBSA), and polyhydroxyalkanol (hereinafter abbreviated as PHA). Further PHAs include poly(3-hydroxybutyrate) (hereinafter abbreviated as PHB), poly(3-hydroxybutyrate / 3-hydroxyvalerate) (hereinafter abbreviated as PHBV), poly(3-hydroxybutyrate / 3-hydroxyhexanoate) (hereinafter abbreviated as PHBH), and poly(3-hydroxybutyrate / 4-hydroxybutyrate).
[0004] These biodegradable resins not only differ in the rate and rate of biodegradation of the resin alone, but also in mechanical properties such as tensile elongation at break and flexural modulus. Therefore, in general, they are used in combination with other resins or mixed with other secondary materials and additives to improve physical properties such as mechanical strength according to the application and location of use.
[0005] Conventionally, resin compositions in which a cellulose-based material is blended with a biodegradable resin have been proposed to improve biodegradability, mechanical strength, etc. For example, Patent Document 1 discloses a resin composition comprising an aliphatic polyester carbonate, which is a polymer having an aliphatic ester structure, and less than 5% by weight of a polymer having a cellulose ester structure with a substitution degree of 1.0 to 3.0, in order to obtain a highly biodegradable resin composition. The resin composition of Patent Document 1 is excellent in mechanical properties such as moldability and tear strength, but it is disclosed that if the resin composition contains 5% by weight or more of a polymer having a cellulose ester structure, the mechanical properties, moldability, and biodegradability are inferior.
[0006] Patent Document 2 discloses a composition containing a cellulose resin in which some or all of the hydroxyl groups of cellulose are acylated, etherified or grafted, and a linear aliphatic polyester or a crosslinked product thereof. Specifically, compositions of cellulose acetate propionate, cellulose acetate butyrate, cardanol-grafted cellulose acetate propionate, and the like, and polybutylene succinate adipate or polybutylene succinate are disclosed. Patent Document 2 describes that, from the viewpoints of water resistance, mechanical properties, heat resistance, and the like, the average number of substituents of the hydroxyl groups per glucose unit of the cellulose resin (hydroxyl group substitution degree) is preferably 1.0 or more and 2.8 or less, and therefore the average number of remaining hydroxyl groups per glucose unit (hydroxyl group residual degree) is preferably 0.9 or less, more preferably 0.7 or less.
[0007] Furthermore, Patent Document 3 discloses a resin composition in which a biodegradable liquid crystal polymer is blended with a biodegradable polymer as a resin composition with improved physical properties without impairing biodegradability, specifically, a resin composition in which a biodegradable liquid crystal polymer having biodegradability is blended with a glucose-sebacic acid copolymer or a biodegradable polymer such as polylactic acid, and a butyric acid ester of hydroxyethyl cellulose or a butyl ether compound of hydroxypropyl cellulose is blended as a biodegradable liquid crystal polymer. [Prior art documents] [Patent documents]
[0008] [Patent Document 1] JP 2000-345012 A [Patent Document 2] International Publication No. 2014 / 119657 [Patent Document 3] JP 2002-275379 A Summary of the Invention [Problem to be solved by the invention]
[0009] Environmentally friendly plastic materials and products require a high degree of plant-based (bio-) content and a high level of biodegradability. In addition, there is a demand for materials that can be biodegraded under home composting conditions, which are more difficult to decompose than industrial composting conditions for soil biodegradation, and for materials that can be biodegraded in the ocean.
[0010] The resin compositions and molded articles made from the same described in Patent Documents 1 to 3 above have improved compatibility between the biodegradable resin and the cellulosic material, and have improved mechanical strength to a certain extent, but their biodegradability in soil under home composting conditions is insufficient.
[0011] The present invention has been made in view of the above background, and an object of the present invention is to provide a biodegradable resin composition containing a biodegradable resin such as an aliphatic polyester resin, an aliphatic-aromatic polyester resin, or an aliphatic oxycarboxylic acid resin, and a cellulose material, which has good compatibility and good biodegradability, and a molded article thereof. [Means for solving the problem]
[0012] As a result of extensive research to solve the above-mentioned problems, the inventors, based on the idea that the modifying groups of cellulose in cellulose derivatives to be blended with biodegradable resins contribute to the compatibility and biodegradability of the biodegradable resin, focused on cellulose derivatives having a specific structure, in particular the average number of carbon atoms per glucose unit and the average number of hydroxyl groups per glucose unit in the cellulose derivative, and found that by setting these values within specific ranges, it is possible to obtain a biodegradable resin composition and molded articles thereof which have a certain or higher biodegradation rate even under home composting conditions and also have good compatibility, and thus arrived at the present invention. That is, the gist of the present invention resides in the following [1] to [7].
[0013] [1] A biodegradable resin composition comprising a biodegradable resin (X) and a cellulose derivative (Y), wherein the average number of hydroxyl groups per glucose unit in the cellulose derivative (Y) is 1.5 or more and 4.0 or less, and the average number of carbon atoms per glucose unit in the cellulose derivative (Y) is 8 or more and 30 or less.
[0014] [2] The biodegradable resin composition according to [1], wherein the cellulose derivative (Y) is at least one selected from the group consisting of cellulose acetate, alkyl cellulose, hydroxyalkyl cellulose, and alkyl esters of oxidized cellulose.
[0015] [3] The biodegradable resin composition according to [1] or [2], comprising 0.5 to 250 parts by mass of the cellulose derivative (Y) per 100 parts by mass of the biodegradable resin (X).
[0016] [4] The biodegradable resin composition according to any one of [1] to [3], wherein the biodegradable resin (X) is at least one selected from the group consisting of an aliphatic polyester resin (A), an aliphatic-aromatic polyester resin (B), an aliphatic oxycarboxylic acid resin (C) and a polyhydroxyalkanoate (D).
[0017] [5] The biodegradable resin composition according to [4], wherein the aliphatic polyester resin (A) contains, as main constituent units, a repeating unit derived from an aliphatic diol and a repeating unit derived from an aliphatic dicarboxylic acid.
[0018] [6] The biodegradable resin composition according to [4] or [5], wherein the aliphatic-aromatic polyester resin (B) contains, as main constituent units, a repeating unit derived from an aliphatic diol, a repeating unit derived from an aliphatic dicarboxylic acid, and a repeating unit derived from an aromatic dicarboxylic acid.
[0019] [7] A biodegradable resin molded article which is an extrusion or injection molded article of the biodegradable resin composition according to any one of [1] to [6]. Effect of the Invention
[0020] The biodegradable resin composition of the present invention has good biodegradability even under home composting conditions, and is therefore more easily applicable as a home composting material than conventional biodegradable resins. In addition, the compatibility between the biodegradable resin (X) and the cellulose derivative (Y) is also good, and therefore the molded product has excellent appearance and feel. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS
[0021] DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS The present invention will be described in detail below with reference to the preferred embodiments. The present invention is not limited to the following description, and can be modified as desired without departing from the scope of the present invention. In this specification, when a numerical value or physical property value is enclosed by "~", the value before and after the "~" is included.
[0022] [Biodegradable resin composition] The biodegradable resin composition of the present invention contains a biodegradable resin (X) and a specific cellulose derivative (Y).
[0023] [Biodegradable resin (X)] The biodegradable resin (X) used in the present invention will be described below. The biodegradable resin (X) of the present invention (hereinafter sometimes referred to as "biodegradable resin (X) of the present invention") may be a known biodegradable resin or biodegradable plastic. The biodegradable resin (X) of the present invention is preferably at least one selected from the group consisting of an aliphatic polyester resin (A), an aliphatic-aromatic polyester resin (B), an aliphatic oxycarboxylic acid resin (C) and a polyhydroxyalkanoate (D). The polyhydroxyalkanoate (D) is also a type of aliphatic oxycarboxylic acid resin (C).
[0024] In addition, the aliphatic polyester resin (A), the aliphatic-aromatic polyester resin (B), the aliphatic oxycarboxylic acid resin (C), and the polyhydroxyalkanoate (D) are each polymers having repeating units, and each repeating unit is also called a compound unit corresponding to the compound from which the repeating unit is derived. For example, a repeating unit derived from an aliphatic diol is also called an "aliphatic diol unit", a repeating unit derived from an aliphatic dicarboxylic acid is also called an "aliphatic dicarboxylic acid unit", and a repeating unit derived from an aromatic dicarboxylic acid is also called an "aromatic dicarboxylic acid unit". Furthermore, the "main structural unit" in the aliphatic polyester resin (A), the aliphatic-aromatic polyester resin (B), the aliphatic oxycarboxylic acid resin (C), and the polyhydroxyalkanoate (D) generally refers to a structural unit that is contained in the polyester resin in an amount of 80 mass% or more, and there are cases in which no structural units other than the main structural unit are contained at all.
[0025] <Aliphatic polyester resin (A)> The aliphatic polyester resin (A) used in the present invention is preferably an aliphatic polyester resin containing an aliphatic diol unit and an aliphatic dicarboxylic acid unit as main constituent units.
[0026] The aliphatic polyester resin (A) used in the present invention preferably has a ratio of succinic acid units in all dicarboxylic acid units of 5 mol% or more and 100 mol% or less. The aliphatic polyester resin (A) may be a mixture of aliphatic polyester resins having different amounts of succinic acid units, and for example, it is also possible to blend an aliphatic polyester resin that does not contain aliphatic dicarboxylic acid units other than succinic acid (containing only succinic acid units as aliphatic dicarboxylic acid units) with an aliphatic polyester resin that contains aliphatic dicarboxylic acid units other than succinic acid, and adjust the amount of succinic acid units in the aliphatic polyester resin (A) to within the above-mentioned preferred range.
[0027] More specifically, the aliphatic polyester resin (A) is a polyester resin containing an aliphatic diol unit represented by the following formula (1) and an aliphatic dicarboxylic acid unit represented by the following formula (2). -OR 1 -O- (1) -OC-R 2 -CO- (2)
[0028] In formula (1), R 1 represents a divalent aliphatic hydrocarbon group. 2 represents a divalent aliphatic hydrocarbon group. The aliphatic diol unit and the aliphatic dicarboxylic acid unit represented by the above formula (1) and (2) may be derived from a compound derived from petroleum or a compound derived from a plant raw material, but are preferably derived from a compound derived from a plant raw material.
[0029] When the aliphatic polyester resin (A) is a copolymer, the aliphatic polyester resin (A) may contain two or more types of aliphatic diol units represented by formula (1), and the aliphatic polyester resin (A) may contain two or more types of aliphatic dicarboxylic acid units represented by formula (2).
[0030] As described above, the aliphatic dicarboxylic acid unit represented by formula (2) preferably contains succinic acid units in an amount of 5 mol% or more and 100 mol% or less based on the total dicarboxylic acid units. By setting the amount of succinic acid constituent units in the aliphatic polyester resin (A) within the above-mentioned range, it is possible to obtain a biodegradable resin composition that is excellent in moldability, heat resistance, and decomposability as well. For the same reason, the amount of succinic acid units in the aliphatic polyester resin (A) is preferably 10 mol% or more, more preferably 50 mol% or more, even more preferably 64 mol% or more, and particularly preferably 68 mol% or more based on the total dicarboxylic acid units. Hereinafter, the ratio of succinic acid units to all dicarboxylic acid units in the aliphatic polyester resin (A) may be referred to as the "succinic acid unit amount".
[0031] In addition, the aliphatic dicarboxylic acid unit represented by formula (2) more preferably contains one or more kinds of aliphatic dicarboxylic acid units other than succinic acid in an amount of 5 mol% to 50 mol% based on the total dicarboxylic acid units. By copolymerizing the aliphatic dicarboxylic acid units other than succinic acid within the above-mentioned predetermined range, the crystallization degree of the aliphatic polyester resin (A) can be reduced, and the biodegradation rate can be increased. For the same reason, the amount of the aliphatic dicarboxylic acid units other than succinic acid in the aliphatic polyester resin (A) is preferably 10 mol% to 45 mol%, more preferably 15 mol% to 40 mol%, based on the total dicarboxylic acid units.
[0032] The aliphatic diol that gives the diol unit represented by formula (1) is not particularly limited, but from the viewpoint of moldability and mechanical strength, an aliphatic diol having 2 to 10 carbon atoms is preferred, and an aliphatic diol having 4 to 6 carbon atoms is particularly preferred. For example, ethylene glycol, 1,3-propanediol, 1,4-butanediol, 1,4-cyclohexanedimethanol, etc. are included, and among them, 1,4-butanediol is particularly preferred. Note that two or more kinds of the above aliphatic diols can be used.
[0033] The aliphatic dicarboxylic acid component that gives the aliphatic dicarboxylic acid unit represented by formula (2) is not particularly limited, but is preferably an aliphatic dicarboxylic acid having 2 to 40 carbon atoms or a derivative such as an alkyl ester thereof, and particularly preferably an aliphatic dicarboxylic acid having 4 to 10 carbon atoms or a derivative such as an alkyl ester thereof. Examples of aliphatic dicarboxylic acids having 4 to 10 carbon atoms other than succinic acid or a derivative such as an alkyl ester thereof include adipic acid, suberic acid, sebacic acid, dodecanedioic acid, dimer acid, etc., and derivatives such as alkyl ester thereof, among which adipic acid and sebacic acid are preferred, and adipic acid is particularly preferred. The above aliphatic dicarboxylic acid components can be used in combination of two or more kinds, and in this case, a combination of succinic acid and adipic acid is preferred.
[0034] The aliphatic polyester resin (A) may have a repeating unit (aliphatic oxycarboxylic acid unit) derived from an aliphatic oxycarboxylic acid. Specific examples of the aliphatic oxycarboxylic acid component that gives the aliphatic oxycarboxylic acid unit include, for example, lactic acid, glycolic acid, 2-hydroxy-n-butyric acid, 2-hydroxycaproic acid, 6-hydroxycaproic acid, 2-hydroxy-3,3-dimethylbutyric acid, 2-hydroxy-3-methylbutyric acid, 2-hydroxyisocaproic acid, and the like, or derivatives thereof such as lower alkyl esters or intramolecular esters. When optical isomers exist in these, they may be any of D-form, L-form, or racemic form, and may be in the form of a solid, liquid, or aqueous solution. Among these, lactic acid or glycolic acid or derivatives thereof are particularly preferred. These aliphatic oxycarboxylic acids may be used alone or as a mixture of two or more.
[0035] When the aliphatic polyester resin (A) contains these aliphatic oxycarboxylic acid units, from the viewpoint of moldability, the content thereof is preferably 20 mol % or less, more preferably 10 mol % or less, even more preferably 5 mol % or less, and most preferably 0 mol % (not included), based on 100 mol % of all constituent units constituting the aliphatic polyester resin (A).
[0036] The melt viscosity of the aliphatic polyester resin (A) may be increased by copolymerizing a trifunctional or higher aliphatic polyhydric alcohol, a trifunctional or higher aliphatic polycarboxylic acid or its acid anhydride, or a trifunctional or higher aliphatic polyoxycarboxylic acid component.
[0037] Specific examples of trifunctional aliphatic polyhydric alcohols include trimethylolpropane, glycerin, etc., and specific examples of tetrafunctional aliphatic polyhydric alcohols include pentaerythritol, etc. These may be used alone or in combination of two or more. A specific example of a trifunctional aliphatic polycarboxylic acid or its anhydride is propanetricarboxylic acid or its anhydride, and a specific example of a tetrafunctional polycarboxylic acid or its anhydride is cyclopentanetetracarboxylic acid or its anhydride, etc. These may be used alone or in combination of two or more.
[0038] In addition, trifunctional aliphatic oxycarboxylic acids are divided into (i) a type having two carboxyl groups and one hydroxyl group in the same molecule, and (ii) a type having one carboxyl group and two hydroxyl groups. Either type can be used, but from the viewpoint of moldability, mechanical strength, and appearance of molded products, (i) a type having two carboxyl groups and one hydroxyl group in the same molecule, such as malic acid, is preferred, and more specifically, malic acid is preferably used. In addition, tetrafunctional aliphatic oxycarboxylic acid components are divided into (i) a type having three carboxyl groups and one hydroxyl group in the same molecule, (ii) a type having two carboxyl groups and two hydroxyl groups in the same molecule, and (iii) a type having three hydroxyl groups and one carboxyl group in the same molecule. Either type can be used, but those having multiple carboxyl groups are preferred, and more specifically, citric acid, tartaric acid, etc. can be mentioned. These can be used alone or in a mixture of two or more types.
[0039] When the aliphatic polyester resin (A) contains such structural units derived from trifunctional or higher components, the content thereof, based on all structural units constituting the aliphatic polyester resin (A) being 100 mol %, is generally 0 mol % or more in lower limit, preferably 0.01 mol % or more in upper limit, and generally 5 mol % or less, preferably 2.5 mol % or less in upper limit.
[0040] The method for producing the aliphatic polyester resin (A) according to the present invention can adopt a known method for producing polyester. In addition, the polycondensation reaction at this time can set appropriate conditions that have been used in the past, and is not particularly limited. Usually, a method is adopted in which the polymerization degree is further increased by carrying out a decompression operation after the esterification reaction has progressed.
[0041] In the case where a diol component forming a diol unit and a dicarboxylic acid component forming a dicarboxylic acid unit are reacted during the production of the aliphatic polyester resin (A), the amounts of the diol component and the dicarboxylic acid component used are set so that the aliphatic polyester resin (A) produced has a desired composition. Usually, the diol component and the dicarboxylic acid component react in substantially equimolar amounts, but the diol component is usually used in an excess of 1 to 20 mol % over the dicarboxylic acid component because it is distilled off during the esterification reaction.
[0042] When the aliphatic polyester resin (A) contains components (optional components) other than the essential components such as aliphatic oxycarboxylic acid units and polyfunctional component units, the corresponding compounds (monomers and oligomers) are reacted so that the aliphatic oxycarboxylic acid units and polyfunctional component units have the desired compositions. At this time, there is no limitation on the timing and method of introducing the optional components into the reaction system, and they are optional as long as the aliphatic polyester resin (A) suitable for the present invention can be produced.
[0043] For example, the timing and method of introducing the aliphatic oxycarboxylic acid into the reaction system is not particularly limited as long as it is before the polycondensation reaction between the diol component and the dicarboxylic acid component. Examples of the method include (1) a method in which the catalyst is dissolved in an aliphatic oxycarboxylic acid solution in advance and mixed, and (2) a method in which the catalyst is introduced into the reaction system and mixed at the same time when the raw materials are charged.
[0044] The timing of introducing the compound that forms the polyfunctional component unit may be such that it is charged simultaneously with other monomers or oligomers at the initial stage of polymerization, or it may be charged after the ester exchange reaction and before the start of pressure reduction. However, charging the compound simultaneously with other monomers or oligomers is preferred from the viewpoint of process simplification.
[0045] Aliphatic polyester resin (A) is usually produced in the presence of a catalyst. As the catalyst, any catalyst that can be used in the production of known polyester resins can be selected as long as it does not significantly impair the effects of the present invention. For example, metal compounds such as germanium, titanium, zirconium, hafnium, antimony, tin, magnesium, calcium, and zinc are suitable. Among them, germanium compounds and titanium compounds are suitable.
[0046] Examples of germanium compounds that can be used as catalysts include organic germanium compounds such as tetraalkoxygermanium, and inorganic germanium compounds such as germanium oxide and germanium chloride. Among these, germanium oxide, tetraethoxygermanium, and tetrabutoxygermanium are preferred in terms of cost and availability, and germanium oxide is particularly preferred.
[0047] Examples of titanium compounds that can be used as catalysts include organic titanium compounds such as tetraalkoxytitanium compounds such as tetrapropyl titanate, tetrabutyl titanate, tetraphenyl titanate, etc. Among these, tetrapropyl titanate, tetrabutyl titanate, etc. are preferred in terms of cost and availability.
[0048] In addition, other catalysts may be used in combination as long as the object of the present invention is not impaired. The catalysts may be used alone or in any combination and ratio of two or more.
[0049] The amount of catalyst used is arbitrary as long as it does not significantly impair the effects of the present invention, but is usually 0.0005% by mass or more, more preferably 0.001% by mass or more, and usually 3% by mass or less, preferably 1.5% by mass or less, based on the amount of monomer used. If the amount is below the lower limit of this range, the effect of the catalyst may not be exhibited, and if the amount is above the upper limit, the production cost may increase, the obtained polymer may be significantly colored, or the hydrolysis resistance may decrease.
[0050] The timing of introducing the catalyst is not particularly limited as long as it is before the polycondensation reaction, and it may be introduced when the raw materials are charged, or may be introduced when the pressure reduction is started. When the aliphatic oxycarboxylic acid unit is introduced, it is preferable to introduce it simultaneously with a monomer or oligomer that forms an aliphatic oxycarboxylic acid unit, such as lactic acid or glycolic acid, when the raw materials are charged, or to dissolve the catalyst in an aqueous aliphatic oxycarboxylic acid solution and introduce it, and in particular, the method of dissolving the catalyst in an aqueous aliphatic oxycarboxylic acid solution and introducing it is preferable in terms of increasing the polymerization rate.
[0051] The reaction conditions such as temperature, polymerization time, and pressure when producing the aliphatic polyester resin (A) are arbitrary as long as they do not significantly impair the effects of the present invention. The reaction temperature of the esterification reaction and / or transesterification reaction between the dicarboxylic acid component and the diol component is usually 150°C or more, preferably 180°C or more, and usually 260°C or less, preferably 250°C or less. The reaction atmosphere is usually an inert atmosphere such as nitrogen or argon. The reaction pressure is usually normal pressure to 10 kPa, and normal pressure is preferable. The reaction time is usually 1 hour or more, and usually 10 hours or less, preferably 6 hours or less, more preferably 4 hours or less. If the reaction temperature is too high, excessive generation of unsaturated bonds occurs, gelation caused by the unsaturated bonds occurs, and polymerization control may become difficult.
[0052] In addition, the pressure for the polycondensation reaction after the esterification reaction and / or transesterification reaction between the dicarboxylic acid component and the diol component is usually at a lower limit of 0.01×10 3 Pa or more, preferably 0.03×10 3 Pa or higher, with an upper limit of 1.4×10 3 Pa or less, preferably 0.4×10 3It is desirable to carry out the reaction under a vacuum of 0.1 Pa or less. The lower limit of the reaction temperature is usually 150° C. or more, preferably 180° C. or more, and the upper limit is usually 260° C. or less, preferably 250° C. or less. The lower limit of the reaction time is usually 2 hours or more, and the upper limit is usually 15 hours or less, preferably 10 hours or less. If the reaction temperature is too high, gelation caused by the unsaturated bonds due to excessive generation of unsaturated bonds may occur, making it difficult to control the polymerization.
[0053] When producing the aliphatic polyester resin (A), a chain extender such as a carbonate compound or a diisocyanate compound can also be used. In this case, the amount of the chain extender is usually 10 mol% or less, preferably 5 mol% or less, and more preferably 3 mol% or less, as the ratio of carbonate bonds or urethane bonds in the aliphatic polyester resin (A) when the total structural units constituting the aliphatic polyester resin are 100 mol%. However, if urethane bonds or carbonate bonds are present in the aliphatic polyester resin (A), biodegradability may be inhibited. Therefore, in the present invention, the carbonate bonds are less than 1 mol%, preferably 0.5 mol% or less, more preferably 0.1 mol% or less, and the urethane bonds are 0.55 mol% or less, preferably 0.3 mol% or less, more preferably 0.12 mol% or less, and even more preferably 0.05 mol% or less, relative to the total structural units constituting the aliphatic polyester resin (A). This amount is 0.9 parts by mass or less, preferably 0.5 parts by mass or less, more preferably 0.2 parts by mass or less, and further preferably 0.1 parts by mass or less, calculated per 100 parts by mass of the aliphatic polyester resin (A). In particular, if the amount of urethane bonds exceeds the upper limit, the decomposition of the urethane bonds may cause problems in the film formation process, such as smoke or odor from the molten film exiting the die, and film breakage due to foaming may occur in the molten film, making it impossible to mold stably. The carbonate bond amount and urethane bond amount in the aliphatic polyester resin (A) are 1 H-NMR and 13 It can be determined by calculation from the results of NMR measurements such as C-NMR.
[0054] Specific examples of carbonate compounds as the chain extender include diphenyl carbonate, ditolyl carbonate, bis(chlorophenyl) carbonate, m-cresyl carbonate, dinaphthyl carbonate, dimethyl carbonate, diethyl carbonate, dibutyl carbonate, ethylene carbonate, diamyl carbonate, dicyclohexyl carbonate, etc. In addition, carbonate compounds consisting of the same or different hydroxy compounds derived from hydroxy compounds such as phenols and alcohols can also be used.
[0055] Specific examples of the diisocyanate compound include known diisocyanates such as 2,4-tolylene diisocyanate, a mixture of 2,4-tolylene diisocyanate and 2,6-tolylene diisocyanate, 1,5-naphthylene diisocyanate, xylylene diisocyanate, hydrogenated xylylene diisocyanate, hexamethylene diisocyanate, isophorone diisocyanate, 4,4'-dicyclohexylmethane diisocyanate, tetramethylxylylene diisocyanate, 2,4,6-triisopropylphenyl diisocyanate, 4,4'-diphenylmethane diisocyanate, and tolidine diisocyanate.
[0056] Other chain extenders such as dioxazoline and silicate esters may also be used. Specific examples of silicate esters include tetramethoxysilane, dimethoxydiphenylsilane, dimethoxydimethylsilane, and diphenyldihydroxysilane.
[0057] It is also possible to produce high molecular weight polyester resins using these chain extenders (coupling agents) using conventional techniques. The chain extender is added to the reaction system in a homogeneous molten state without a solvent after the polycondensation is completed, and is reacted with the polyester obtained by the polycondensation.
[0058] More specifically, a polyester resin having a higher molecular weight can be obtained by reacting the chain extender with a polyester having a terminal group substantially containing a hydroxyl group and a weight average molecular weight (Mw) of 20,000 or more, preferably 40,000 or more, obtained by catalytically reacting a diol component with a dicarboxylic acid component. A prepolymer having a weight average molecular weight of 20,000 or more can be produced by using a small amount of chain extender without generating gel during the reaction, since it is not affected by the remaining catalyst even under severe conditions such as a molten state. Here, the weight average molecular weight (Mw) of the polyester resin is calculated as a monodisperse polystyrene conversion value from the measured value by gel permeation chromatography (GPC) at a measurement temperature of 40°C using chloroform as a solvent.
[0059] Therefore, for example, when the polyester resin is further increased in molecular weight using the above-mentioned diisocyanate compound as a chain extender, it is preferable to use a prepolymer having a weight average molecular weight of 20,000 or more, preferably 40,000 or more. If the weight average molecular weight is less than 20,000, the amount of diisocyanate compound used for increasing the molecular weight increases, and the heat resistance may decrease. Using such a prepolymer, a polyester resin having urethane bonds having a linear structure linked via urethane bonds derived from the diisocyanate compound is produced.
[0060] The pressure during chain extension is usually 0.01 MPa or more and 1 MPa or less, preferably 0.05 MPa or more and 0.5 MPa or less, more preferably 0.07 MPa or more and 0.3 MPa or less, and most preferably normal pressure.
[0061] The reaction temperature during chain extension has a lower limit of usually 100° C. or more, preferably 150° C. or more, more preferably 190° C. or more, and most preferably 200° C. or more, and an upper limit of usually 250° C. or less, preferably 240° C. or less, and more preferably 230° C. or less. If the reaction temperature is too low, the viscosity will be high, making it difficult to achieve a uniform reaction, and high stirring power will tend to be required, while if the reaction temperature is too high, gelation or decomposition of the polyester resin will tend to occur concomitantly.
[0062] The time for chain extension is usually 0.1 minutes or more, preferably 1 minute or more, more preferably 5 minutes or more, and usually 5 hours or less, preferably 1 hour or less, more preferably 30 minutes or less, and most preferably 15 minutes or less. If the time for chain extension is too short, the effect of adding the chain extender tends not to be exerted, and if it is too long, gelation or decomposition of the polyester resin tends to occur concomitantly.
[0063] The molecular weight of the aliphatic polyester resin (A) used in the present invention can be measured by gel permeation chromatography (GPC). The weight average molecular weight (Mw) of the aliphatic polyester resin (A) using monodisperse polystyrene as the standard is usually 10,000 or more and 1,000,000 or less, but is preferably 20,000 or more and 500,000 or less, and more preferably 50,000 or more and 400,000 or less, because this is advantageous in terms of moldability and mechanical strength.
[0064] The melt flow rate (MFR) of the aliphatic polyester resin (A) is a value measured at 190°C under a load of 2.16 kg according to JIS K7210 (1999), and is usually 0.1 g / 10 min to 100 g / 10 min, but from the viewpoints of moldability and mechanical strength, it is preferably 50 g / 10 min or less, particularly preferably 40 g / 10 min or less. The MFR of the aliphatic polyester resin (A) can be adjusted by the molecular weight.
[0065] The melting point of the aliphatic polyester resin (A) is preferably 70° C. or higher, more preferably 75° C. or higher, and is preferably 170° C. or lower, more preferably 150° C. or lower, and particularly preferably lower than 130° C. When there are multiple melting points, it is preferable that at least one of the melting points is within the above range. The elastic modulus of the aliphatic polyester resin (A) is preferably 180 to 1000 MPa. If the melting point is outside the above range, moldability is poor, if the elastic modulus is less than 180 MPa, problems are likely to occur in moldability, and if the elastic modulus exceeds 1000 MPa, the impact strength tends to deteriorate.
[0066] The method for adjusting the melting point and elastic modulus of the aliphatic polyester resin (A) is not particularly limited. For example, the melting point and elastic modulus can be adjusted by selecting the type of copolymerization component of the aliphatic dicarboxylic acid component other than succinic acid, adjusting the copolymerization ratio of each, or combining them.
[0067] In the present invention, the aliphatic polyester resin (A) is not limited to one type, and a blend of two or more types of aliphatic polyester resins (A) differing in the types and ratios of constituent units, production methods, physical properties, etc. may be used.
[0068] <Aliphatic-aromatic polyester resin (B)> Examples of the aliphatic-aromatic polyester resin (B) include those in which at least a portion of the repeating units of the above-mentioned aliphatic polyester resin (A) have been replaced with aromatic compound units, preferably polyester resins containing aliphatic diol units, aliphatic dicarboxylic acid units and aromatic dicarboxylic acid units as main constituent units, in which a portion of the aliphatic dicarboxylic acid units of the above-mentioned aliphatic polyester resin (A) have been replaced with aromatic dicarboxylic acid units.
[0069] Examples of the aromatic compound unit include an aromatic diol unit having an aromatic hydrocarbon group which may have a substituent, an aromatic dicarboxylic acid unit having an aromatic hydrocarbon group which may have a substituent, an aromatic dicarboxylic acid unit having an aromatic heterocyclic group which may have a substituent, and an aromatic oxycarboxylic acid unit having an aromatic hydrocarbon group which may have a substituent. The aromatic hydrocarbon group and the aromatic heterocyclic group may be a single ring, or may be a ring in which a plurality of rings are bonded to each other or condensed. Specific examples of the aromatic hydrocarbon group include a 1,2-phenylene group, a 1,3-phenylene group, a 1,4-phenylene group, a dinaphthylene group, and a diphenylene group. Specific examples of the aromatic heterocyclic group include a 2,5-furandiyl group.
[0070] Specific examples of aromatic dicarboxylic acid components that provide aromatic dicarboxylic acid units include terephthalic acid, isophthalic acid, naphthalenedicarboxylic acid, diphenyldicarboxylic acid, 2,5-furandicarboxylic acid, etc. Among these, terephthalic acid is preferred.
[0071] The aromatic dicarboxylic acid component may be a derivative of an aromatic dicarboxylic acid compound. For example, the derivatives of the aromatic dicarboxylic acid components exemplified above are preferred, and among them, lower alkyl esters having 1 to 4 carbon atoms and acid anhydrides are exemplified. Specific examples of the derivatives of aromatic dicarboxylic acid compounds include lower alkyl esters such as methyl esters, ethyl esters, propyl esters, and butyl esters of the aromatic dicarboxylic acid components exemplified above; cyclic acid anhydrides of the aromatic dicarboxylic acid components exemplified above, such as succinic anhydride; and the like. Among them, dimethyl terephthalate is preferred.
[0072] Specific examples of aromatic diol components that provide aromatic diol units include xylylene glycol, 4,4'-dihydroxybiphenyl, 2,2-bis(4'-hydroxyphenyl)propane, 2,2-bis(4'-β-hydroxyethoxyphenyl)propane, bis(4-hydroxyphenyl)sulfone, and bis(4-β-hydroxyethoxyphenyl)sulfonic acid. The aromatic diol component may be a derivative of an aromatic diol compound. It may also be a compound having a structure in which a plurality of aliphatic diol compounds and / or aromatic diol compounds are dehydrated and condensed with each other.
[0073] Specific examples of aromatic oxycarboxylic acid components that provide aromatic oxycarboxylic acid units include p-hydroxybenzoic acid, p-β-hydroxyethoxybenzoic acid, etc. The aromatic oxycarboxylic acid component may be a derivative of an aromatic oxycarboxylic acid compound. It may also be a compound (oligomer) having a structure in which a plurality of aliphatic oxycarboxylic acid compounds and / or aromatic oxycarboxylic acid compounds are dehydrated and condensed with each other. That is, an oligomer may be used as a raw material.
[0074] When the aromatic compound component that gives these aromatic compound units has optical isomers, any of D-form, L-form, and racemic form may be used. In addition, the aromatic compound component is not limited to the above examples as long as it can give aromatic compound units. Furthermore, the aromatic compound component may be used alone or in any combination and ratio of two or more kinds.
[0075] As the aliphatic-aromatic polyester resin (B), it is preferable to use an aromatic dicarboxylic acid component as a component that gives aromatic compound units, and in this case, the content of the aromatic dicarboxylic acid unit is preferably 10 mol% or more and 80 mol% or less based on the total amount of the aliphatic dicarboxylic acid unit and the aromatic dicarboxylic acid unit (100 mol%). In addition, it is preferable to use terephthalic acid or 2,5-furandicarboxylic acid as the aromatic dicarboxylic acid component, and in this case, it is preferable that the aliphatic-aromatic polyester resin (B) is a polybutylene terephthalate adipate and / or polybutylene terephthalate succinate resin. In addition, as the aliphatic-aromatic polyester resin (B), polyethylene-2,5-furandicarboxylate resin and polybutylene-2,5-furandicarboxylate resin are preferable, and polybutylene-2,5-furandicarboxylate / succinate, which has excellent biodegradability, is particularly preferable.
[0076] The aliphatic-aromatic polyester resin (B) can be produced in the same manner as the aliphatic polyester resin (A) described above, using at least an aromatic compound component as a raw material.
[0077] The molecular weight of the aliphatic-aromatic polyester resin (B) used in the present invention can be measured by gel permeation chromatography (GPC). The weight average molecular weight (Mw) of the aliphatic-aromatic polyester resin (B) using monodisperse polystyrene as the standard is usually 10,000 or more and 1,000,000 or less, but is preferably 30,000 or more and 800,000 or less, and more preferably 50,000 or more and 600,000 or less, because this is advantageous in terms of moldability and mechanical strength.
[0078] The melt flow rate (MFR) of the aliphatic-aromatic polyester resin (B) is a value measured at 190°C under a load of 2.16 kg according to JIS K7210 (1999), and is usually 0.1 g / 10 min to 100 g / 10 min, but from the viewpoints of moldability and mechanical strength, it is preferably 50 g / 10 min or less, and particularly preferably 30 g / 10 min or less. The MFR of the aliphatic-aromatic polyester resin (B) can be adjusted by the molecular weight.
[0079] The melting point of the aliphatic-aromatic polyester resin (B) is usually 60° C. or higher, preferably 70° C. or higher, more preferably 80° C. or higher, and preferably 150° C. or lower, more preferably 140° C. or lower, particularly preferably 120° C. or lower. When there are multiple melting points, it is preferable that at least one of the melting points is within the above range. The elastic modulus of the aliphatic-aromatic polyester resin (B) is preferably 180 to 1000 MPa. If the melting point is outside the above range, moldability is poor, if the elastic modulus is less than 180 MPa, problems are likely to occur in moldability, and if the elastic modulus exceeds 1000 MPa, the impact strength tends to deteriorate.
[0080] The method for adjusting the melting point and elastic modulus of the aliphatic-aromatic polyester resin (B) is not particularly limited. For example, the melting point and elastic modulus can be adjusted by selecting the type of copolymerization component of the aliphatic dicarboxylic acid component other than the aromatic dicarboxylic acid component, adjusting the copolymerization ratio of each, or combining them.
[0081] In the present invention, the aliphatic-aromatic polyester resin (B) is not limited to one type, and two or more types of aliphatic-aromatic polyester resins (B) differing in the types and ratios of constituent units, production methods, physical properties, etc., can be blended and used.
[0082] <Aliphatic oxycarboxylic acid resin (C) · Polyhydroxyalkanoate (D)> The aliphatic oxycarboxylic acid resin (C) used in the present invention has an aliphatic oxycarboxylic acid unit as a main constituent unit, and the aliphatic oxycarboxylic acid unit is preferably represented by the following formula (3). -OR 3 -CO- (3) (In the above formula (3), R 3 represents a divalent aliphatic hydrocarbon group or a divalent alicyclic hydrocarbon group.
[0083] Specific examples of the aliphatic oxycarboxylic acid component that gives the aliphatic oxycarboxylic acid unit of formula (3) include lactic acid, glycolic acid, 2-hydroxy-n-butyric acid, 2-hydroxycaproic acid, 2-hydroxy-3,3-dimethylbutyric acid, 2-hydroxy-3-methylbutyric acid, 2-hydroxyisocaproic acid, and mixtures thereof. When optical isomers exist in these, either D-form or L-form may be used. Among these, preferred are lactic acid and glycolic acid. Two or more of these aliphatic oxycarboxylic acid components may be used in combination.
[0084] As the aliphatic oxycarboxylic acid resin (C), polylactic acid (PLA) is particularly preferable.
[0085] Furthermore, a urethane bond, an amide bond, a carbonate bond, an ether bond, etc. can be introduced into the aliphatic oxycarboxylic acid resin (C) to the extent that it does not affect biodegradability.
[0086] The method for producing the aliphatic oxycarboxylic acid resin (C) is not particularly limited, and it can be produced by a known method such as a direct polymerization method of oxycarboxylic acid or a ring-opening polymerization method of a cyclic substance.
[0087] The molecular weight of the aliphatic oxycarboxylic acid resin (C) used in the present invention can be measured by gel permeation chromatography (GPC). The weight average molecular weight (Mw) of the resin using monodisperse polystyrene as the standard is usually 10,000 or more and 1,000,000 or less, but is preferably 20,000 or more and 500,000 or less, and more preferably 50,000 or more and 400,000 or less, because this is advantageous in terms of moldability and mechanical strength.
[0088] The melt flow rate (MFR) of the aliphatic oxycarboxylic acid resin (C) is a value measured at 190°C under a load of 2.16 kg according to JIS K7210 (1999), and is usually 0.1 g / 10 min to 100 g / 10 min, but from the viewpoints of moldability and mechanical strength, it is preferably 50 g / 10 min or less, and particularly preferably 40 g / 10 min or less. The MFR of the aliphatic oxycarboxylic acid resin (C) can be adjusted by the molecular weight.
[0089] The melting point of the aliphatic oxycarboxylic acid resin (C) is preferably 70° C. or higher, more preferably 75° C. or higher, and is preferably 170° C. or lower, more preferably 150° C. or lower, and particularly preferably lower than 130° C. When there are multiple melting points, it is preferable that at least one of the melting points is within the above range. The elastic modulus of the aliphatic oxycarboxylic acid resin (C) is preferably 180 to 1000 MPa. If the melting point is outside the above range, moldability is poor, if the elastic modulus is less than 180 MPa, problems are likely to occur in moldability, and if the elastic modulus exceeds 1000 MPa, the impact strength tends to deteriorate.
[0090] The method for adjusting the melting point and elastic modulus of the aliphatic oxycarboxylic acid resin (C) is not particularly limited. For example, the melting point and elastic modulus can be adjusted by selecting the type of copolymerization component other than the aliphatic oxycarboxylic acid, adjusting the copolymerization ratio of each component, or combining them.
[0091] As the aliphatic oxycarboxylic acid resin (C), polyhydroxyalkanoate (D) described below can also be preferably used. The polyhydroxyalkanoate (hereinafter sometimes referred to as PHA) (D) preferably used in the present invention is an aliphatic polyester containing a repeating unit represented by the general formula: [-CHR-CH2-CO-O-] (wherein R is an alkyl group having 1 to 15 carbon atoms), and is a copolymer containing 3-hydroxybutyrate units and 3-hydroxyhexanoate units as main constituent units.
[0092] From the viewpoint of moldability and thermal stability, the polyhydroxyalkanoate (D) used in the present invention preferably contains 80 mol% or more, more preferably 85 mol% or more, of 3-hydroxybutyrate units as a constituent component. Also, it is preferable that it is produced by a microorganism. Specific examples of the polyhydroxyalkanoate (D) include poly(3-hydroxybutyrate-co-3-hydroxyhexanoate) copolymer resin, poly(3-hydroxybutyrate-co-3-hydroxyvalerate-co-3-hydroxyhexanoate) copolymer resin, etc. In particular, from the viewpoints of molding processability and physical properties of the resulting molded article, poly(3-hydroxybutyrate-co-3-hydroxyhexanoate) copolymer resin, ie, PHBH, is preferred.
[0093] In the polyhydroxyalkanoate (D), the composition ratio of 3-hydroxybutyrate (hereinafter sometimes referred to as 3HB) and the copolymerized comonomer such as 3-hydroxyhexanoate (hereinafter sometimes referred to as 3HH), i.e., the monomer ratio in the copolymer resin, is preferably 3-hydroxybutyrate / comonomer=97 / 3 to 80 / 20 (mol% / mol%), more preferably 95 / 5 to 85 / 15 (mol% / mol%), from the viewpoint of molding processability and molded product quality. If the comonomer ratio is less than 3 mol%, molding may be difficult because the molding temperature and the thermal decomposition temperature are close to each other. If the comonomer ratio exceeds 20 mol%, the crystallization of the polyhydroxyalkanoate (D) may be delayed, resulting in poor productivity.
[0094] The ratio of each monomer in the polyhydroxyalkanoate (D) can be measured by gas chromatography as follows. To approximately 20 mg of dried PHA, 2 ml of a sulfuric acid / methanol mixture (15 / 85 (mass ratio)) and 2 ml of chloroform are added, the container is sealed, and heated at 100°C for 140 minutes to obtain the methyl ester of the PHA decomposition product. After cooling, 1.5 g of sodium bicarbonate is gradually added to neutralize the mixture, and the mixture is left to stand until the evolution of carbon dioxide gas stops. After adding 4 ml of diisopropyl ether and mixing well, the monomer unit composition of the PHA decomposition product in the supernatant is analyzed by capillary gas chromatography to determine the ratio of each monomer in the copolymer resin.
[0095] The weight average molecular weight (hereinafter sometimes referred to as Mw) of the polyhydroxyalkanoate (D) used in the present invention can be measured by the above-mentioned gel permeation chromatography (GPC), and the weight average molecular weight (Mw) using monodisperse polystyrene as the standard substance is usually 200,000 or more and 2,500,000 or less, but is preferably 250,000 or more and 2,000,000 or less, more preferably 300,000 or more and 1,000,000 or less, because it is advantageous in terms of moldability and mechanical strength. If the weight average molecular weight is less than 200,000, the mechanical properties may be poor, and if it exceeds 2,500,000, molding processing may be difficult.
[0096] The melt flow rate (MFR) of the polyhydroxyalkanoate (D) is a value measured at 190°C under a load of 2.16 kg according to JIS K7210 (1999), and is preferably 1 g / 10 min to 100 g / 10 min, but from the viewpoints of moldability and mechanical strength, it is more preferably 80 g / 10 min or less, and particularly preferably 50 g / 10 min or less. The MFR of the polyhydroxyalkanoate (D) can be adjusted by the molecular weight.
[0097] The melting point of the polyhydroxyalkanoate (D) is preferably 100° C. or higher, more preferably 120° C. or higher, and is preferably 180° C. or lower, more preferably 170° C. or lower, and particularly preferably lower than 160° C. When there are multiple melting points, it is preferable that at least one of the melting points is within the above range.
[0098] Polyhydroxyalkanoate (D) is produced by, for example, a microorganism such as Alcaligenes eutrophus AC32 strain, which is obtained by introducing a PHA synthase gene derived from Aeromonas caviae into Alcaligenes eutrophus (international deposit under the Budapest Treaty, international depository authority: National Institute of Advanced Industrial Science and Technology Patent Organism Depositary Center (6-1-1 Central, Higashi 1-chome, Tsukuba City, Ibaraki Prefecture, Japan), original deposit date: August 12, 1996, transferred on August 7, 1997, deposit number FERM BP-6038 (transferred from original deposit FERM P-15786)) (J. Bacteriol., 179, 4821 (1997)). As the polyhydroxyalkanoate (D), commercially available products can be used. Commercially available polyhydroxyalkanoates (D) containing 3-hydroxybutyrate units and 3-hydroxyhexanoate units as main constituent units include "PHBH X331N", "PHBH X131A", "PHBH X151A" and the like manufactured by Kaneka Corporation.
[0099] In the present invention, the aliphatic oxycarboxylic acid resin (C), including the polyhydroxyalkanoate (D), is not limited to one type, and two or more types of aliphatic oxycarboxylic acid resins (C) differing in the types of constituent units, the ratio of constituent units, the production method, physical properties, etc., can be blended and used.
[0100] [Cellulose derivatives (Y)] The cellulose derivative (Y) used in the present invention (hereinafter sometimes referred to as "cellulose derivative (Y) of the present invention") has an average number of hydroxyl groups per glucose unit in the cellulose derivative (Y), i.e., the average number of hydroxyl groups, of 1.5 or more and 4.0 or less, and an average number of carbon atoms per glucose unit in the cellulose derivative (Y), i.e., the average number of carbon atoms, of 8 or more and 30 or less.
[0101] Unsubstituted cellulose has three hydroxyl groups and six carbon atoms per glucose unit. The cellulose derivative (Y) of the present invention is prepared by introducing an appropriate substituent into the hydroxyl groups of cellulose. In this case, the substituents are randomly introduced into the three hydroxyl groups present per glucose unit. When unsubstituted cellulose is acylated or alkyl-etherified, only one substituent can be introduced into one hydroxyl group. The amount of introduced substituents is generally expressed as the average number of hydroxyl groups into which a substituent has been introduced per glucose unit, and is called the degree of substitution (DS). DS has a value in the range of 0 to 3. On the other hand, when hydroxyalkyl-etherification is performed, a substituent can be further introduced into the hydroxyl group present in the hydroxyalkyl group, so that two or more substituents may be introduced into one hydroxyl group of cellulose. In this case, the amount of introduced substituents is generally expressed as the average number of substituents bonded to one glucose unit, and is called the degree of molar substitution (MS). MS can have a value greater than 3. The cellulose derivative (Y) of the present invention is not particularly limited in terms of the type of substituent, DS, or MS, so long as the average number of carbon atoms and the average number of hydroxyl groups per glucose unit satisfy the above-mentioned conditions.
[0102] <Average number of carbon atoms and average number of hydroxyl groups of cellulose derivative (Y)> In the present invention, the number of carbon atoms and the number of hydroxyl groups per glucose unit of the cellulose derivative (Y) can be determined by determining the average number of substituents (DS or MS) per glucose unit by a conventionally known method depending on the type of substituent, adding up the numbers of carbon atoms and hydroxyl groups contained in the substituents to the number of carbon atoms (6) and the number of hydroxyl groups (3) contained in glucose, respectively, and subtracting the number of hydroxyl groups consumed in the substitution reaction. For example, in the case of hydroxypropyl cellulose, if MS is a, the number of carbon atoms in the hydroxypropyl group is 3 and the number of hydroxyl groups is 1, so Average number of carbon atoms = 6 + 3 × a Average number of hydroxyl groups=3+1×aa On the other hand, for example, in the case of cellulose acetate, if DS is b, the number of carbon atoms in the acetyl group is 2 and the number of hydroxyl groups is 0, so Average number of carbon atoms = 6 + 2 × b Average number of hydroxyl groups=3+0×bb It can be calculated from each equation.
[0103] The average number of substituents is a value specific to the cellulose derivative. When the substituents are alkyl ethers and / or hydroxyalkyl ethers, the average number of substituents can be determined by the method described in, for example, JP-A-62-151745: 13 It can be determined by measuring C-NMR. In addition, for hydroxypropyl cellulose or hydroxypropyl methylcellulose, it can also be determined by converting the mass ratio of hydroxypropoxy groups and methoxy groups determined according to the 17th Revised Japanese Pharmacopoeia into a molar ratio. In this method, the content of each substituent is determined by decomposing a sample with hydroiodic acid and quantifying the resulting isopropyl iodide and iodomethane by gas chromatography.
[0104] When the substituents are esters, for example, the compound is dissolved in a suitable solvent, then reacted with sodium hydroxide to hydrolyze the compound, and the remaining sodium hydroxide is titrated with sulfuric acid to determine the average number of substituents. The composition ratio of the substituents can be determined by measuring the solution after titration using ion chromatography or gas chromatography. In addition, the compound can be dissolved in a suitable heavy solvent to determine the average number of substituents. 1 It can also be determined from the integral ratio by measuring H-NMR.
[0105] The average number of carbon atoms in the cellulose derivative (Y) of the present invention is 8 or more, preferably 10 or more, and more preferably 12 or more. On the other hand, the average number of carbon atoms in the cellulose derivative (Y) of the present invention is 30 or less, preferably 25 or less, and more preferably 20 or less. If the average number of carbon atoms is less than 8, the affinity with the biodegradable resin (X) is poor, and good appearance and smoothness when formed into a film cannot be obtained. If the average number of carbon atoms is more than 30, the heat resistance is poor.
[0106] The average number of hydroxyl groups of the cellulose derivative (Y) of the present invention is 1.5 or more, preferably 2.0 or more, more preferably 2.2 or more. On the other hand, the average number of hydroxyl groups of the cellulose derivative (Y) of the present invention is 4.0 or less, preferably 3.8 or less, more preferably 3.5 or less. If the average number of hydroxyl groups is less than 1.5, biodegradability is insufficient. If the average number of hydroxyl groups is more than 4.0, heat resistance and compatibility may be poor.
[0107] As the cellulose derivative (Y) of the present invention, it is preferable to use one or more selected from the group consisting of cellulose acetate, alkyl cellulose, hydroxyalkyl cellulose, and alkyl ester of oxidized cellulose. Specifically, for example, in the case of cellulose acetate, the degree of acetyl substitution is about 1.1 to 1.5. In addition, in the case of alkyl cellulose, hydroxyalkyl cellulose, alkyl ester of oxidized cellulose, etc., methyl cellulose, ethyl cellulose, hydroxyethyl cellulose, hydroxypropyl cellulose, hydroxypropyl methyl cellulose, dihydroxypropyl cellulose, etc. are listed. Among these, hydroxyalkyl cellulose is preferable, and hydroxypropyl cellulose is particularly preferable.
[0108] The shape of the cellulose derivative (Y) of the present invention is not particularly limited, and may be any shape such as powder, granules, fibers, etc. From the viewpoint of uniform mixing, the particle size is preferably 150 μm or less, more preferably 50 μm or less.
[0109] The cellulose derivative (Y) of the present invention may be used alone or in any combination and ratio of two or more different ones having different types, amounts of introduced substituents, shapes, etc.
[0110] [Content of biodegradable resin (X) and cellulose derivative (Y)] The biodegradable resin composition of the present invention is a composition containing a biodegradable resin (X) and the above-mentioned cellulose derivative (Y) of the present invention, and preferably contains 0.5 parts by mass or more and 250 parts by mass or less of the cellulose derivative (Y) per 100 parts by mass of the biodegradable resin (X). In the biodegradable resin composition of the present invention, if the content of the cellulose derivative (Y) of the present invention per 100 parts by mass of the biodegradable resin (X) is 0.5 parts by mass or more, the effect of increasing the bio content to a certain level or more can be expected. On the other hand, if the content of the cellulose derivative (Y) of the present invention is 250 parts by mass or less, the mechanical properties of the obtained molded article are not impaired.
[0111] The biodegradable resin composition of the present invention preferably contains 1 to 150 parts by mass, and even more preferably 3 to 100 parts by mass, of the cellulose derivative (Y) of the present invention per 100 parts by mass of the biodegradable resin (X).
[0112] [Other ingredients] In addition to the cellulose derivative (Y) of the present invention, the biodegradable resin composition of the present invention may contain, as "other components", one or more of various additives such as a filler, a plasticizer, an antistatic agent, an antioxidant, a light stabilizer, an ultraviolet absorber, a dye, a pigment, an antihydrolysis agent, a crystal nucleating agent, an antiblocking agent, a weather resistance agent, a heat stabilizer, a flame retardant, a release agent, an antifogging agent, a surface wetting improver, an incineration aid, a dispersing aid, various surfactants, and a slip agent. The biodegradable resin composition of the present invention may also contain functional additives such as a freshness-preserving agent and an antibacterial agent.
[0113] These other components can be blended as desired within the range that does not impair the effects of the present invention, and one type may be used alone, or two or more types may be used in combination.
[0114] In order not to impair the physical properties of the biodegradable resin composition of the present invention, it is usually preferable that the total amount of these other components in the biodegradable resin composition of the present invention is 0.01 mass% or more and 40 mass% or less relative to the total amount of the biodegradable resin composition of the present invention.
[0115] [Method for producing biodegradable resin composition] The biodegradable resin composition of the present invention is produced by kneading the above-mentioned biodegradable resin (X) and the cellulose derivative (Y) of the present invention in a kneader and dispersing the biodegradation promoter in the biodegradable resin. In addition, other resins and other components used as necessary may be mixed in the kneader together with the biodegradable resin (X) and the cellulose derivative (Y).
[0116] This mixing step is carried out by mixing the biodegradable resin (X), the cellulose derivative (Y), and other resins and other components used as necessary in a predetermined ratio simultaneously or in any order using a mixer such as a tumbler, V-type blender, Nauta mixer, Banbury mixer, kneading roll, or extruder, and preferably further melt-kneading the mixture.
[0117] The kneader used in the mixing step may be a melt kneader. The extruder may be either a twin screw extruder or a single screw extruder, with a twin screw extruder being more preferred.
[0118] The temperature during melt kneading is preferably 160 to 230°C. This temperature range makes it possible to shorten the time required for the melting reaction, and prevents deterioration of the resin and deterioration of color tone due to carbonization of the biodegradation promoter, and also improves practical physical properties such as impact resistance and moist heat resistance by uniformly mixing. From the same viewpoint, the melt kneading temperature is more preferably 170 to 220°C.
[0119] As for the melt-kneading time, from the viewpoint of more reliably avoiding resin deterioration, etc., it is necessary to avoid an unnecessary long time, and it is preferably from 20 seconds to 20 minutes, more preferably from 30 seconds to 15 minutes. Therefore, it is preferable to set the melt-kneading temperature and time conditions so as to satisfy these melt-kneading conditions.
[0120] [Biodegradable resin molded body] The biodegradable resin composition of the present invention can be molded by various molding methods applied to general-purpose plastics. Examples of the molding methods include compression molding (compression molding, lamination molding, stampable molding), injection molding, extrusion molding, and co-extrusion molding (film molding by inflation method or T-die method, laminate molding, pipe molding, electric wire / cable molding, molding of profiled materials), heat press molding, hollow molding (various blow moldings), calendar molding, solid molding (uniaxial stretch molding, biaxial stretch molding, roll rolling molding, stretch-oriented nonwoven fabric molding, thermoforming (vacuum molding, compressed air molding), plastic processing, powder molding (rotational molding), and various nonwoven fabric moldings (dry method, adhesion method, entanglement method, spunbond method, etc.). Among them, injection molding, extrusion molding, compression molding, or heat press molding, especially extrusion molding or injection molding, are preferably applied. Specific shapes are preferably applied to sheets, films, and containers.
[0121] Furthermore, the biodegradable resin molded article of the present invention obtained by molding the biodegradable resin composition of the present invention can be subjected to various secondary processing for the purpose of imparting surface functions such as chemical functions, electrical functions, magnetic functions, mechanical functions, friction / wear / lubrication functions, optical functions, thermal functions, biocompatibility, etc. Examples of secondary processing include embossing, painting, adhesion, printing, metallizing (plating, etc.), machining, surface treatment (antistatic treatment, corona discharge treatment, plasma treatment, photochromism treatment, physical vapor deposition, chemical vapor deposition, coating, etc.), etc.
[0122] [Application] The biodegradable resin molded article of the present invention made of the biodegradable resin composition of the present invention is suitably used in a wide range of applications, such as packaging materials for packaging liquids, powders, and solids, such as various foods, medicines, and miscellaneous goods, agricultural materials, and construction materials, etc. Specific applications include injection molded articles (e.g., fresh food trays, fast food containers, coffee capsule containers, cutlery, outdoor leisure products, etc.), extrusion molded articles (e.g., films, sheets, fishing lines, fishing nets, vegetation nets, secondary processing sheets, water-retaining sheets, etc.), and hollow molded articles (bottles, etc.). Further examples include agricultural films, coating materials, fertilizer coating materials, seedling pots, laminated films, plates, stretched sheets, monofilaments, nonwoven fabrics, flat yarns, staples, crimped fibers, striped tapes, split yarns, composite fibers, blown bottles, shopping bags, garbage bags, compost bags, cosmetic containers, detergent containers, bleach containers, ropes, binding materials, sanitary cover stock materials, cooler boxes, cushioning films, multifilaments, synthetic paper, and medical applications such as surgical thread, sutures, artificial bones, artificial skin, DDS such as microcapsules, and wound dressings.
[0123] The biodegradable resin molded article of the present invention is particularly suitable for food containers such as food packaging films, trays for fresh food, fast food containers, and lunch boxes. EXAMPLES
[0124] The present invention will be described in more detail below using examples and comparative examples, but the present invention is not limited to the following examples as long as it does not exceed the gist of the invention. The values of various production conditions and evaluation results in the following examples are meant as preferred upper or lower limit values in the embodiment of the present invention, and the preferred range may be a range defined by a combination of the above-mentioned upper or lower limit values and the values of the following examples or values between the examples.
[0125] [Average number of carbon atoms and hydroxyl groups per glucose unit of cellulose derivative (Y)] The average number of carbon atoms and the average number of hydroxyl groups per glucose unit of the cellulose derivative (Y) can be calculated using the above-mentioned calculation formula. When the substituents are alkyl ethers and / or hydroxyalkyl ethers, the average number of substituents in the calculation formula can be calculated, for example, by the method described in JP-A-62-151745: 13 It can be determined by measuring C-NMR. In addition, for hydroxypropyl cellulose or hydroxypropyl methylcellulose, it can also be determined by converting the mass ratio of hydroxypropoxy groups and methoxy groups determined according to the 17th Revised Japanese Pharmacopoeia into a molar ratio. In this method, a sample is decomposed with hydroiodic acid, and the resulting isopropyl iodide and iodomethane are quantified by gas chromatography to determine the content of each substituent. When the substituents are esters, for example, the compound is dissolved in a suitable solvent, then reacted with sodium hydroxide to hydrolyze the compound, and the remaining sodium hydroxide is titrated with sulfuric acid to determine the average number of substituents. The composition ratio of the substituents can be determined by measuring the solution after titration using ion chromatography or gas chromatography. In addition, the compound can be dissolved in a suitable heavy solvent to determine the average number of substituents. 1 It can also be determined from the integral ratio by measuring H-NMR.
[0126] [Biodegradable resin (X)] As the biodegradable resin (X), the following aliphatic polyester resin (A) was used. Aliphatic polyester resin (A): Polybutylene succinate adipate (PBSA) PTMCCBiochem Product name: BioPBS TM FD92PB" Melting point: 89℃
[0127] [Cellulose derivatives (Y)] As the cellulose derivative (Y) of the present invention, the following cellulose derivative (Y-1) was used. Cellulose derivatives (Y-1): Hydroxypropyl cellulose "NISSO HPC SSL SFP" manufactured by Nippon Soda Co., Ltd. Average number of substituents: 3.6
[0128] [Cellulose and other cellulose derivatives] As the cellulose derivatives and celluloses other than the cellulose derivative (Y) of the present invention, the following were used. Cellulose: "KC Flock W-400Y" manufactured by Nippon Paper Industries Co., Ltd. Cellulose derivatives (1): Hydroxypropyl cellulose "LODICEL LDC-L" manufactured by Shin-Etsu Chemical Co., Ltd. Average number of substituents: 0.2 Cellulose derivatives (2): Hydroxypropyl methylcellulose "Metolose 60SH-03" manufactured by Shin-Etsu Chemical Co., Ltd. Average number of substituents: Hydroxypropyl groups: 0.2 Methyl group: 1.9 Cellulose derivatives (3): Ethyl cellulose Dow Chemical Company "Ethocel Std 7" Average number of substituents: 2.5 Cellulose derivatives (4): Cellulose acetate propionate Eastman Chemical Company "CAP-482-20" Average number of substituents: acetyl group: 0.09 Propionyl group: 2.3
[0129] Table 1 shows the average numbers of carbon atoms and hydroxyl groups of the cellulose derivative (Y), cellulose and other cellulose derivatives, together with the calculation formulas.
[0130] [Table 1]
[0131] [Example 1, Comparative Examples 1 to 6] Aliphatic polyester resin (A) and cellulose or a cellulose derivative were blended in the ratio shown in Table 2 (except for Comparative Example 1, in which only aliphatic polyester resin (A) was used), and melt-kneaded for 4 minutes at 170°C under a nitrogen atmosphere using a small twin-screw kneader (DSM's "Xplore Micro 15cc Twin Screw Compounder"). The obtained resin composition was molded into a sheet having a thickness of about 120 μm using a hot press molding machine at 180°C.
[0132] The obtained resin composition sheet was subjected to the following evaluations. The results are shown in Table 2.
[0133] <Biodegradable> The obtained resin composition sheet was cut into a rectangle of 50 mm x 30 mm, and buried in a mixture of gardening soil (Iris Ohyama Corporation's "Flower and Vegetable Culture Soil") with a moisture content of 20% RH and compost (Yawata Bussan Corporation's inoculant source for biodegradation testing) in a 1:1 mass ratio contained in a polyethylene Tupperware container, the lid was closed, and the container was left to stand for 42 days in an incubator at 28°C. The weight change before and after standing was measured, and the weight retention rate (the ratio (percentage) of the mass after the test to the mass before the test) was calculated and evaluated on the following four-point scale. ◎: Weight retention rate less than 10% 〇: Weight retention rate is 10% or more and less than 30% △: Weight retention rate is 30% or more and less than 70% ×: Weight retention rate 70% or more
[0134] <compatibility> The appearance of the obtained resin composition sheet was visually observed and rated on the following three-level scale. : Transparent to semi-transparent, no visible particles. ○: Translucent, and slight scattering by particles can be seen when held up to light. ×: Semi-transparent, particles clearly visible.
[0135] [Table 2]
[0136] As is clear from Table 2, by using a specific cellulose derivative (Y) whose average number of hydroxyl groups and average number of carbon atoms are within the specified ranges, the resin composition with the biodegradable resin (X) has a high bio-content, a certain level of biodegradability, and excellent compatibility, so that the appearance and feel are also good.
Claims
1. A biodegradable resin composition comprising a biodegradable resin (X) and a cellulose derivative (Y), wherein the average number of hydroxyl groups per glucose unit in the cellulose derivative (Y) is 1.5 or more and 4.0 or less, and the average number of carbon atoms per glucose unit in the cellulose derivative (Y) is 8 or more and 30 or less, The biodegradable resin composition, wherein the biodegradable resin (X) is at least one selected from the group consisting of an aliphatic polyester resin (A) and an aliphatic-aromatic polyester resin (B).
2. 2. The biodegradable resin composition according to claim 1, wherein the cellulose derivative (Y) is at least one selected from the group consisting of cellulose acetate, alkyl cellulose, hydroxyalkyl cellulose, and alkyl esters of oxidized cellulose.
3. The biodegradable resin composition according to claim 1 or 2, comprising 0.5 to 250 parts by mass of the cellulose derivative (Y) relative to 100 parts by mass of the biodegradable resin (X).
4. The biodegradable resin composition according to any one of claims 1 to 3, wherein the aliphatic polyester resin (A) contains, as main structural units, a repeating unit derived from an aliphatic diol and a repeating unit derived from an aliphatic dicarboxylic acid.
5. The biodegradable resin composition according to any one of claims 1 to 4, wherein the aliphatic-aromatic polyester resin (B) contains a repeating unit derived from an aliphatic diol, a repeating unit derived from an aliphatic dicarboxylic acid, and a repeating unit derived from an aromatic dicarboxylic acid as main structural units.
6. A biodegradable resin molded article which is an extrusion molded or injection molded article of the biodegradable resin composition according to any one of claims 1 to 5.
Citation Information
Patent Citations
Photosensitive resin composition for forming relief plate
JP1980153935A
Thermoplastic biodegradable polysaccharide ester / polysaccharide ether ester having maleic acid adduct group
JP1997052903A
Resin composition
JP2000345012A
Resin composition and its molding method, and recycling method of resin composition
JP2002275379A
Thermally shrinkable film for container lid material, and container lid material using thermally shrinkable film
JP2006273346A